A review of wideband reflectarray antennas for 5G communication systems - Dahri, Muhammad Hashim; Jamaluddin, Mohd Haizal; Abbasi, Muhammad Inam; Kamarudin, Muhammad Ramlee (Institute of Electrical and Electronics Engineers (IEEE), 2017)
The advancement in the current communication technology makes it incumbent to analyze the conventional features of reflectarray antenna for future adaptability. This work thoroughly reviews the design and experimental features of reflectarray antenna for its bandwidth improvement in microwave and millimeter wave frequency ranges. The paper surveys the fundamental and advanced topologies of reflectarray design implementations which are needed particularly for its broadband features. The realization of its design approaches has been studied at unit cell and full reflectarray levels for its bandwidth enhancement. Various design configurations have also been critically analyzed for the compatibility with the high frequency 5G systems.
Keywords: reflectarrays; bandwidth; unit cell; multiresonance; millimeter wave; 5G